Characterization of Polysulfides, Polysulfanes, and Other Unique Species in the Reaction between GSNO and H2S - Murugaeson R Kumar; Patrick J Farmer (Molecules, 2019)
Glutathione-based products, GSnX, of the reaction of hydrogen sulfide, H2S, S-nitroso glutathione, and GSNO, at varied stoichiometries have been analyzed by liquid chromatography high-resolution mass spectrometry (LC-HRMS) and chemical trapping experiments. A wide variety of glutathione-based species with catenated sulfur chains have been identified including sulfanes (GSSnG), sulfides (GSSnH), and sulfenic acids (GSnOH); sulfinic (GSnO2H) and sulfonic (GSnO3H) acids are also seen in reactions exposed to air. The presence of each species of GSnX within the original reaction mixtures was confirmed using Single Ion Chromatograms (SICs), to demonstrate the separation on the LC column, and given approximate quantification by the peak area of the SIC. Further, confirmation for different GSnX families was obtained by trapping with species-specific reagents. Several unique GSnX families have been characterized, including bridging mixed di- and tetra-valent polysulfanes and internal trithionitrates (GSNHSnH) with polysulfane branches. Competitive trapping experiments suggest that the polysulfane chains are formed via the intermediacy of sulfenic acid species, GSSnOH. In the presence of radical trap vinylcyclopropane (VCP) the relative distributions of polysulfane speciation are relatively unaffected, suggesting that radical coupling is not a dominant pathway. Therefore, we suggest polysulfane catenation occurs via reaction of sulfides with sulfenic acids.